Assessing the sediment quality of the Laje de Santos marine state park and other marine protected areas of the central coast of Sao Paulo (Brazil) - Abessa, Denis [UNESP]; Vicente, Thaisa Marques; Moreira, Lucas Buruaem [UNESP]; Morais, Lucas Goncalves; Feitosa Cruz, Ana Carolina [UNESP]; Massonetto, Mirella [UNESP]; Campos, Bruno Galvao de [UNESP]; Bicego, Marcia Caruso; Taniguchi, Satie; Hortellani, Marcos Antonio; Souza Sarkis, Jorge Eduardo de (Inst Oceanografico, Univ Sao Paulo, 2017)
In this study, the quality of sediments from three Marine Protected Areas (MPAs) located on the coast of Sao Paulo (Laje de Santos Marine State Park - PEMLS; Xixova-Japui State Park - XJSP; and Central Coast Marine Protection Area - APAMLC) was assessed. Four sampling surveys were conducted (September/October 2013; January 2014; July 2014; January 2015). Sediment samples were collected at10 sites, distributed along the 3 MPAs. Samples were analyzed for sediment texture, total organic carbon, CaCO3, metals, aliphatic and polycyclic aromatic hydrocarbons, and for whole-sediment and sediment-water interface toxicities. Principal component analysis (PCA) was used to integrate data. Most of the sediments exhibited low concentrations of chemicals, with the exception of those from P2 (APAMLC) where moderate levels of contaminants were detected. Sediments from P7 and P9 (PEMLS) occasionally showed signs of petroleum hydrocarbons. The other sediments showed no relevant contamination but presented variable toxicity, especially those of bioclastic composition. The PCA indicated a contribution of the sediment properties to the toxicities, especially the CaCO3. In bioclastic sediments, toxicity might be due to physical causes by or any indirect factor such as the presence of ammonia. It was concluded that both natural and anthropic factors are causing toxicity in sediments from the MPAs studied.
Keywords: Toxicity; Metals; Hydrocarbons; Marine Protected Area; Sediment